2018
DOI: 10.1186/s12906-018-2171-3
|View full text |Cite
|
Sign up to set email alerts
|

Fructus Ligustri Lucidi modulates estrogen receptor expression with no uterotrophic effect in ovariectomized rats

Abstract: BackgroundAccumulating evidence suggests that Fructus Ligustri Lucidi (FLL) plays a beneficial role in preventing the development of osteoporosis. However, the effects of FLL on estrogen receptor (ER) α and ERβ expressions remain unknown. Therefore, in the current study we attempted to probe into the effects of FLL on ERα and ERβ expressions in femurs, tibias and uteri of ovariectomized (OVX) rats.MethodsThe OVX rats were orally administrated with FLL water extract (3.5 g/kg/day) for 12 weeks. The uteri, femur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
(41 reference statements)
3
5
0
Order By: Relevance
“…In the current study, we found that FLL preserved femoral bone mass and strength as well as restored femoral bone microarchitectures in OVX rats without affecting uterus weight, which is in consistence with our previous publication (Tang et al, 2018) and the investigation from other research group (Chen et al, 2017). In addition, salidroside, an identified compound in FLL aqueous extract and medicated serum, has been demonstrated to attenuate bone histological changes and prevent bone loss (Zheng, Qi, & Chen, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, we found that FLL preserved femoral bone mass and strength as well as restored femoral bone microarchitectures in OVX rats without affecting uterus weight, which is in consistence with our previous publication (Tang et al, 2018) and the investigation from other research group (Chen et al, 2017). In addition, salidroside, an identified compound in FLL aqueous extract and medicated serum, has been demonstrated to attenuate bone histological changes and prevent bone loss (Zheng, Qi, & Chen, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Many active ingredients of LLF including tyrosol, hydroxytyrosol, salidroside, oleonuezhenide, and nuezhenoside G13 exhibit antioxidative activity, which is one of the most important mechanisms of LLF in treating OP [ 41 ]. Aqueous extract of LLF can improve bone microstructure of OVX-induced postmenopausal OP rats through suppressing oxidative stress response and increasing ER α expression in the femurs and tibias [ 13 , 42 ]. Therefore, antioxidative activity and phytoestrogen property may be the mechanisms by which EF and LLF synergistically treat OP.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological studies show that EF, LLF, and their active ingredients (such as icariin and baohuoside I in EF and oleanolic acid and ursolic acid in LLF) have anti-OP effects through improving bone microstructure, increasing bone mineral density, and promoting the differentiation and proliferation of OBs [9][10][11][12]. The water extract of LLF can upregulate ERα expression of femurs and tibias of ovariectomy-(OVX-) induced OP rats [13]; EF has the estrogen-like effect which is one of the most important mechanisms of EF in treating OP [14]. This may be the mechanism by which EF and LLF synergistically treat OP.…”
Section: Introductionmentioning
confidence: 99%
“…The model rats subjected to OVX were classified into 3 categories randomly, namely, OVX group ( n = 12), estradiol valerate (EV) group ( n = 12) and DIO group ( n = 12). According to studies published previously [ 21 23 ], EV group rats were administered oral gavage of EV (0.1 mg/kg body weight, Bayer Health Care, Guangzhou, China) every day, while DIO group rats were treated by oral gavage with DIO (100 mg/kg body weight, purity≥93%, Sigma-Aldrich, Saint Louis, MO, USA) every day. For the SHAM or OVX group, rats were administered distilled water (of equal volume) by oral gavage.…”
Section: Methodsmentioning
confidence: 99%